2021
DOI: 10.3390/brainsci11111439
|View full text |Cite
|
Sign up to set email alerts
|

Use of Functional Near-Infrared Spectroscopy to Predict and Measure Cochlear Implant Outcomes: A Scoping Review

Abstract: Outcomes following cochlear implantation vary widely for both adults and children, and behavioral tests are currently relied upon to assess this. However, these behavioral tests rely on subjective judgements that can be unreliable, particularly for infants and young children. The addition of an objective test of outcome following cochlear implantation is therefore desirable. The aim of this scoping review was to comprehensively catalogue the evidence for the potential of functional near infrared spectroscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 133 publications
0
14
0
Order By: Relevance
“…The available studies show contradictory findings. A recent review states that it is important to discuss the methodological aspects of such functional neuroimaging examinations [ 22 - 26 , 46 , 47 , 50 ]. One problem with measuring functional brain activation is that many variables must be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available studies show contradictory findings. A recent review states that it is important to discuss the methodological aspects of such functional neuroimaging examinations [ 22 - 26 , 46 , 47 , 50 ]. One problem with measuring functional brain activation is that many variables must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis to test a 2-sided hypothesis at 95% significance and 80% power showed that we need at least 15 participants with normal hearing to detect auditory activations. In addition, we considered previous findings from auditory fNIRS studies [ 26 , 28 , 31 , 32 ]. We compared the size of their study cohorts, the fNIRS systems used, the optode arrangements used, and the reliability of their results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fNIRS is simple to implement over multiple testing sessions; so, it is ideal for longitudinal designs and may be an important tool to assess the efficacy of hearing devices over time (e.g., before and after cochlear implantation). 102 Sevy et al 103 were the first group to identify a reliable response to speech in auditory cortex for cochlear implant users. Bisconti et al 104 found overall similar activation patterns in auditory and nonauditory regions between cochlear implant users and normal-hearing adults during passive listening to speech, suggesting that hearing loss in adulthood does not significantly alter the neural organization of speech perception.…”
Section: Fnirs and Auditory Cognitive Neurosciencementioning
confidence: 99%
“…As well as the pre-processing, channels with poor signal quality were detected despite the efforts to optimize optode contacts with the scalp. The scalp coupling index (SCI), which can effectively identify poor fNIRS signals in speech perception experiments (Pollonini et al, 2014;Mushtaq et al, 2019Mushtaq et al, , 2021Lawrence et al, 2021), were adopted. The signals with the two wavelengths were first bandpass filtered into 0.5-2.5 Hz that represents the cardiac elements captured by fNIRS and were correlated with each other.…”
mentioning
confidence: 99%